PENGARUH KERJA SAMA TIM DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PT. KOMINDO BIZOLUSI JAKARTA PUSAT - Rima Handayani; Eni Puji Astuti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This research aims to examine the impact of team collaboration and career development on employee job satisfaction at PT. Komindo Bizolusi in Central Jakarta, both individually and collectively. The study employs a quantitative approach, utilizing a saturated sampling technique with a sample size of 75 respondents. Data collection is carried out through questionnaires, and data analysis involves validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Based on the research findings, the following results are revealed: (1) Team collaboration significantly influences employee job satisfaction at PT. Komindo Bizolusi in Central Jakarta, with the t-test value (14.766) exceeding the t-table value (1.993). (2) Career development also significantly impacts employee job satisfaction at PT. Komindo Bizolusi in Central Jakarta, as the t-test value (13.845) surpasses the t-table value (1.960). (3) Simultaneously, team collaboration and career development have a significant combined effect on employee job satisfaction at PT. Komindo Bizolusi in Central Jakarta, with the F-test value (135.125) exceeding the F-table value (2.730).